<htm>Augochlora janae, uma nova espécie de Augochlorini (Hymenoptera: Halictidae)</htm> - Laroca, Sebastião; Buys, Sandor Christiano (Acta Biológica Paranaense, 2013)
<htm>Augochlora janae, uma nova espécie de Augochlorini (Hymenoptera: Halictidae)</htm>